Sexuality in the Frame of Christian Ethics: Student Perspectives and Its Implementation - Zakharia Panggabean; Eni Debora Sihombing (Program Studi Pendidikan Agama Kristen, Fakultas Ilmu Pendidikan Kristen IAKN Tarutung, 2022)
Sex is something special and most important in human life. God wants people to enjoy sexual activity but only in the marriage environment, God forbids sex before marriage to protect people from unwanted pregnancies, save lives, protect babies, and most importantly honor God. However, in reality it is difficult to control yourself in avoiding the temptation to have sex outside of marriage. This research was conducted with the aim of shaping students to be role models for the community and the surrounding environment in empowering Christian education, as well as making premarital sexuality an education and vision with persuasive power for young people's intelligence. This research was conducted using a quantitative approach supported by data analysis and theories related to this research. This research technique was carried out by the questionnaire method (statements to respondents). This study proves that the effect of Christian Ethics education on sex is 42.9%. Thus, we suggest that we better understand or explore the risks of premarital sex and how good relationships should be in accordance with God's teachings.